Ssc-microRNA-132 targets DACH1 to exert anti-inflammatory and anti-apoptotic effects in Clostridium perfringens beta2 toxin-treated porcine intestinal epithelial cells. (February 2022) - Xie, Kaihui; Yan, Zunqiang; Wang, Wei; Luo, Ruirui; Gao, Xiaoli; Wang, Pengfei; Yang, Qiaoli; Huang, Xiaoyu; Zhang, Juanli; Yang, Jiaojiao; Gun, Shuangbao
Abstract: Clostridium perfringens ( C. perfringens ) type C (CPC) is one of the chief pathogens that causes diarrhea in piglets, and C. perfringens beta2 (CPB2) toxin is the main virulence factor of CPC. Our previous research demonstrated that ssc-microR-132 was differentially expressed in ileal tissues of CPC-mediated diarrheic piglets and healthy piglets, which implied a potential role of ssc-microR-132 in this process. Here, we found that ssc-microR-132 was notably down-regulated in CPB2-exposed intestinal porcine epithelial cells (IPEC-J2), which was consistent with the ileal tissue expression. Moreover, ssc-microR-132 upregulation alleviated CPB2-induced inflammatory damage and apoptosis in IPEC-J2, whereas ssc-microR-132 knockdown presented the opposite effects. Furthermore, the dual-luciferase reporter assay indicated that ssc-microR-132 directly targeted Dachshund homolog 1 ( DACH1 ). Moreover, DACH1 overexpression intensified CPB2-induced inflammatory injury and apoptosis in IPEC-J2. Remarkably, the introduction of DACH1 weakened the anti-inflammatory and anti-apoptotic effects of ssc-microR-132 in CPB2-exposed IPEC-J2. Overall, the results reveal that ssc-microR-132 targeted DACH1 to alleviate CPB2-mediated inflammation and apoptosis in IPEC-J2. Highlights: ssc-miR-132 is down-regulated in Clostridium perfringens beta2 (CPB2) toxin induced IPEC-J2 cells. DACH1 is the target gene of ssc-miR-132. ssc-miR-132 targets DACH1 to ameliorate CPB2 toxin-induced inflammation and apoptosis in IPEC-J2 cells.